Consumer Expectations of Online Services in the Insurance Industry: An Exploratory Study of Drivers and Outcomes - Méndez-Aparicio, M. Dolores; Izquierdo-Yusta, Alicia; Jiménez-Zarco, Ana I. (Frontiers in Psychology, 2017)
Today, the customer-brand relationship is fundamental to a company’s bottom line, especially in the service sector and with services offered via online channels. In order to maximize its effects, organizations need (1) to know which factors influence the formation of an individual’s service expectations in an online environment; and (2) to establish the influence of these expectations on customers’ likelihood of recommending a service before they have even used it In accordance with the TAM model (Davis, 1989, 1992), the TRA model (Fishbein and Ajzen, 1975), the extended UTAUT model (Venkatesh et al. 2012), and the approach described by Alloza (2011), this work proposes a theoretical model of the antecedents and consequences of consumer expectations of online services. In order to validate the proposed theoretical model, a sample of individual insurance company customers was analyzed. The results showed, first, the importance of customers’ expectations with regard to the intention to recommend the “private area” of the company’s website to other customers prior to using it themselves. They also revealed the importance to expectations of the antecedents perceived usefulness, ease of use, frequency of use, reputation, and subjective norm